Estimating the Fiscal Effects of Public Pharmaceutical Expenditure Reduction in Greece - Souliotis, Kyriakos; Papageorgiou, Manto; Politi, Anastasia; Frangos, Nikolaos; Tountas, Yiannis (Frontiers in Public Health, 2015)
The purpose of the present study is to estimate the impact of pharmaceutical spending reduction on public revenue, based on data from the national health accounts as well as on reports of Greece’s organizations. The methodology of the analysis is structured in two basic parts. The first part presents the urgency for rapid cutbacks on public pharmaceutical costs due to the financial crisis and provides a conceptual framework for the contribution of the Greek pharmaceutical branch to the country’s economy. In the second part, we perform a quantitative analysis for the estimation of multiplier effects of public pharmaceutical expenditure reduction on main revenue sources, such as taxes and social contributions. We also fit projection models with multipliers as regressands for the evaluation of the efficiency of the particular fiscal measure in the short run. According to the results, nearly half of the gains from the measure’s application is offset by financially equivalent decreases in the government’s revenue, i.e., losses in tax revenues and social security contributions alone, not considering any other direct or indirect costs. The findings of multipliers’ high value and increasing short-term trend imply the measure’s inefficiency henceforward and signal the risk of vicious circles that will provoke the economy’s deprivation of useful resources.